Pengaruh Online Customer Review dan Brand Image Terhadap Keputusan Pembelian Produk Somethinc di Kota Bekasi - Tarisa Agista; Widi Winarso; Kardinah Indrianna Meutia (Manajemen Kreatif Jurnal, 2025)
This study was conducted to determine the effect of online customer reviews and brand image on consumer purchasing decisions of Somethinc products. This study is a quantitative research using a non-probability sampling method with an accidental sampling/incidental sampling technique. In this study, primary data in the form of questionnaires through Google Forms was used. The number of samples used in this study was 96 respondents who were people domiciled in Bekasi City. The analysis technique used in this study uses multiple linear regression analysis with the help of SPSS 26 software. Based on the results of the data processing carried out, the results of this study showed that the Online Customer Review variable has a positive and significant effect on Purchasing Decisions, the Brand Image variable has a positive and significant effect on Purchasing Decisions. The Online Customer Review and Brand Image variables simultaneously have a significant influence on the Purchasing Decision variable.